The inhibition of PGAM5 suppresses seizures in a kainate-induced epilepsy model via mitophagy reduction - Zhong, Fuxin; Gan, Yunhao; Song, Jiaqi; Zhang, Wenbo; Yuan, Shiyun; Qin, Zhangjin; Wu, Jiani; Lü, Yang; Yu, Weihua (Frontiers in Molecular Neuroscience, 2022)
Background: Epilepsy is a common neurological disease, and excessive mitophagy is considered as one of the major triggers of epilepsy. Mitophagy is a crucial pathway affecting reactive oxygen species. Phosphoglycerate mutase 5 (PGAM5) is a protein phosphatase present in mitochondria that regulates many biological processes including mitophagy and cell death. However, the mechanism of PGAM5 in epilepsy remains unclear. The purpose of the present study was to examine whether PGAM5 affects epilepsy through PTEN-induced putative kinase 1 (PINK1)-mediated mitophagy. Methods: After the knockdown of PGAM5 expression by the adeno-associated virus, an epilepsy model was created by kainic acid. Next, the seizure activity was recorded by local field potentials before evaluating the level of mitochondrial autophagy marker proteins. Lastly, the ultrastructure of mitochondria, neuronal damage and oxidative stress levels were further observed. Results: A higher PGAM5 level was found in epilepsy, and its cellular localization was in neurons. The interactions between PGAM5 and PINK1 in epilepsy were further found. After the knockdown of PGAM5, the level of PINK1 and light chain 3B was decreased and the expression of the translocase of the inner mitochondrial membrane 23 and translocase of the outer mitochondrial membrane 20 were both increased. Knockdown of PGAM5 also resulted in reduced neuronal damage, decreased malondialdehyde levels, decreased reactive oxygen species production and increased superoxide dismutase activity. In addition, the duration of spontaneous seizure-like events (SLEs), the number of SLEs and the time spent in SLEs were all reduced in the epilepsy model after inhibition of PGAM5 expression. Conclusion: Inhibition of PGAM5 expression reduces seizures via inhibiting PINK1-mediated mitophagy.